The Dispositive and Inquisitorial Principles of Civil Process - Carrión, Roque (1970)
In this work the author addresses the problem of the truth of the facts and their investigation, as well as the role of the judge in the civil process. To this end, the author carefully studies the principles that guide the civil process: the dispositive principle and the inquisitorial principle. Regarding the former, it can be observed that the judge has, in the process, an attenuated role and a limited focus on the knowledge of the facts. In contrast, the second principle gives the judge greater relevance, giving him the direction of the process in the search for the truth. This is why the author argues that the dispositive principle is insufficient to guarantee the material truth, since the determination of the facts requires greater intervention by the judge. That said, the purpose of this article is to propose a procedural reform of the procedural codes, especially the civil procedure code, which allows the judge to investigate the facts and arrive at the material truth of the facts in the civil process.